Cyclodextrins producting activity of different species of aerobic sporeforming bacteria - Z. G. Avakian; Khachaturyan, A. A.; T. S. Davidyan; M. O. Adamyan (ՀՀ ԳԱԱ հրատ.)
A comprehensive and systematic study of cyclodextrin producting activity of 572 strains of bacilli has carried out.
Keywords: Biology; Biochemistry